STUDI KOMPARASI METODE INTERPOLASI LINIER DAN INTERPOLASI PERSAMAAN BOLA DALAM PERHITUNGAN VOLUMETRIK - , SIGIT NUR IMAN W. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Digital Elevation Model (DEM) is a three-dimensional shape of the Earth's surface represented in a model. One of some methods used to build DEM is interpolation. Each interpolation method brings their own consequences, such as Triangulated Irregular Network (TIN) constructed of irregular flat triangles which theoretically can not represent curvature. On the other hand, there is spherical equation which is theoretically able to cover this shortfall. The study includes a ground surveying using Total Station as the data. The sample is Dome Karst (100 m in diameter) which represents a curved shape and a soccer field that represents a flat shape. Data such as altitude point (x,y,z), they are 60 for Dome Karst and 6 for soccer field . While the test point of accuracy each method are 16 for Dome Karst and 3 for the football field. The data is interpolated by TIN method and spherical equation, then it is calculated as the volume of Dome Karst. DEM formed twice for each of the interpolation method. The results shows that the TIN interpolation can not properly represent the Dome Karst (RMS-Error: 2.368974813), while spherical equation can represent Dome Karst properly (RMS-Error: 2.133816668). Instead , TIN interpolation can represent well the football field (RMS-Error : 0.192333044), while the spherical equation can not represent well the football field (RMS-Error: 2.643165148). There are changes in the accuracy of each interpolation method when the sample points are reducted. With 38 sample points, obtained 4.03952163 of standar deviation of linear interpolation and 3.525802603 of standar deviation of spherical equation interpolation. Dome Karst volume generated from TIN interpolation is 1047,058 m3, while the volume of Dome Karst generated from spherical equation interpolation is 730,8512 m3.